1991
DOI: 10.1002/ppul.1950100109
|View full text |Cite
|
Sign up to set email alerts
|

The effect of triclofos sodium sedation on respiratory rate, oxygen saturation, and heart rate in infants and young children

Abstract: Chloral hydrate is frequently used to sedate infants for lung function testing. While no effect on respiratory function has been demonstrated, a recent study has reported a fall in oxygen saturation (Sa O 2) following sedation in wheezy infants. This study was designed to assess the effects of the closely related but less gastrically irritant drug triclofos sodium on respiratory rate (RR), heart rate (HR), and Sa O 2 in infants without cardiopulmonary disease. Paired measurements using respiratory inductance p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…Sedation was used in this study as most of the infants were aged w3 months and the tidal breathing measurements preceded more complex forced expiratory manoeuvres. Furthermore, chloral hydrate or triclofos, in the doses commonly used for infant lung function tests, appear to have minimal effect on either TPTEF:TE [6] or RR [29,30]. While poorer absorption of sedative could, theoretically, result in lighter sedation in infants with CF, this is unlikely to have influenced the results of the current study, since no differences were observed between the two groups with respect to the duration of sleep induced by sedation and recordings were limited to periods of quiet sleep and regular tidal breathing.…”
Section: Discussionmentioning
confidence: 99%
“…Sedation was used in this study as most of the infants were aged w3 months and the tidal breathing measurements preceded more complex forced expiratory manoeuvres. Furthermore, chloral hydrate or triclofos, in the doses commonly used for infant lung function tests, appear to have minimal effect on either TPTEF:TE [6] or RR [29,30]. While poorer absorption of sedative could, theoretically, result in lighter sedation in infants with CF, this is unlikely to have influenced the results of the current study, since no differences were observed between the two groups with respect to the duration of sleep induced by sedation and recordings were limited to periods of quiet sleep and regular tidal breathing.…”
Section: Discussionmentioning
confidence: 99%
“…Chloral hydrate at doses of 60 -80 mg/kg is described as safe and with minimal alterations in gasometrical and pulmonary variables such as respiratory-system compliance, respiratory drive, and lung volumes. 17,[35][36][37] In a sedated infant, PSE could minimally interfere with respiratory variables, and during clinical practice it is not rare to treat sedated patients. We believe that the chloral hydrate did not affect these variables during our study.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of sedation on ventilation distribution inhomogeneity remains unclear, although values in healthy unsedated infants [26,30] are similar to the results reported here in sedated infants, despite different systems. Chloral hydrate sedation has been shown to have minimal effects on breathing patterns, strength of Hering-Breuer inflation reflex or oxygen saturation in healthy infants during the first 2 years of age [43,44].…”
Section: Paediatric Lung Functionmentioning
confidence: 99%